2012
DOI: 10.1371/journal.pone.0032028
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sCD14 Is Associated with Virological Response to Pegylated-Interferon-Alpha/Ribavirin Treatment in HIV/HCV Co-Infected Patients

Abstract: ObjectivesMicrobial translocation (MT) through the gut accounts for immune activation and CD4+ loss in HIV and may influence HCV disease progression in HIV/HCV co-infection. We asked whether increased MT and immune activation may hamper anti-HCV response in HIV/HCV patients.Methods98 HIV/HCV patients who received pegylated-alpha-interferon (peg-INF-alpha)/ribavirin were retrospectively analyzed. Baseline MT (lipopolysaccharide, LPS), host response to MT (sCD14), CD38+HLA-DR+CD4+/CD8+, HCV genotype, severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
3
27
2
2
Order By: Relevance
“…This is in agreement with a previous study (12). However, Kared et al (25) describes higher proportion of IL-7Ra + HLADR-T cells in SVR compared to non-SVR prior to treatment, and Marchetti et al (28) describes sCD14 as a predictor of early virological response in HIV/HCV co-infected patients. Thus, whether T-cell subsets and/or microbial translocation can be used as a predictor of SVR after interferon treatment must be considered questionable, and larger studies are warranted to investigate this.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with a previous study (12). However, Kared et al (25) describes higher proportion of IL-7Ra + HLADR-T cells in SVR compared to non-SVR prior to treatment, and Marchetti et al (28) describes sCD14 as a predictor of early virological response in HIV/HCV co-infected patients. Thus, whether T-cell subsets and/or microbial translocation can be used as a predictor of SVR after interferon treatment must be considered questionable, and larger studies are warranted to investigate this.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, for 98 HIV/HCV coinfected patients on virologically suppressive ART, we reported increased sCD14 levels in subjects either harboring aggressive HCV genotypes (i.e., genotypes 1 to 4) or presenting with cirrhosis (129). Furthermore, Sandler et al reported that higher sCD14 levels distinguish patients with severe liver fibrosis from those with minimal fibrosis in a cohort of hepatitis B virus (HBV)/HCV-monoinfected subjects (130).…”
Section: Microbial Translocation In Liver Diseasementioning
confidence: 51%
“…Although several factors have been associated with the response to anti-HCV therapy, the determinants of successful full-course peg-IFN-␣-ribavirin therapy are still poorly defined (133)(134)(135)(136)(137). Interestingly, increased plasma sCD14 levels have been proven to be independently associated with poor responses to anti-HCV treatment (129,130), thus suggesting an independent role of microbial translocation in the outcome of anti-HCV therapy. Contrasting data, however, were obtained for a cohort of ART-naïve HIV/ HCV-coinfected patients with high CD4 ϩ T-cell counts, for whom higher sCD14 levels were independently associated with a decreased risk of liver disease progression, defined as a time to Fibrosis 4 (Fib-4) score of Ͼ1.45 or liver-related death.…”
Section: Microbial Translocation In Liver Diseasementioning
confidence: 99%
“…Both Italian and European guidelines recommend that antiretroviral treatment should precede anti-HCV treatment in patients with a supposed rapid progression of HIV disease (HIV-RNA > 100,000 copies/mL or a CD4+ T-cells decay >100 cells/uL in the previous year) at any level of CD4 cell count, and in the case of CD4+ T-cell counts lower than 500 cells/uL because it may help attain a sustained virological response (SVR) [64,65]. Indeed, data from a large observational Italian study on treatment of HCV infection in HIV-infected patients seem to support an earlier start of cART in co-infected subjects undergoing standard anti-HCV treatment (based on peg Interferon and ribavirin), as suppression of HIV-RNA was significantly associated with "eradication" (SVR) of HCV infection [66].…”
Section: Hcv or Hiv Therapy: What To Start First?mentioning
confidence: 99%